Rewriting History: Narrative Resistance and Poetic Justice in Martin McDonagh’s A Very Very Very Dark Matter - Lanters, José (Hungarian Journal of English and American Studies, 2021)
Martin McDonagh’s A Very Very Very Dark Matter (2018) explores how the stories of exploited people have been written out of history. The play includes several storytellers, and it both replicates and deviates from the details of numerous existing narratives, including McDonagh’s own plays. Set in 1857, the play imagines that Hans Christian Andersen’s fairy tales were written by a pygmy woman from the Belgian Congo who has traveled back in time; Hans calls her Marjory and keeps her in a box in his attic. Eventually Marjory writes herself out of the box and departs for Africa to prevent the colonization of her people. Dark Matter compels us to question the narratives about the past that have become embedded in our culture and to uncover the facts that official accounts have altered or suppressed; rewriting history is acceptable only in imaginative storytelling, as an act of poetic justice. (JL)